Effects of clopidogrel on inflammatory cytokines and adhesion molecules in human endothelial cells: Role of nitric oxide mediating pleiotropic effects. Issue 4 (14th July 2017) - Cerda, Alvaro; Pavez, Monica; Manriquez, Victor; Luchessi, Andre Ducati; Leal, Pamela; Benavente, Felipe; Fajardo, Cristina Moreno; Salazar, Luis; Hirata, Mario Hiroyuki; Hirata, Rosario Dominguez Crespo
Summary: Introduction: Clopidogrel is commonly used in prevention and treatment of atherothrombosis. Some previous studies have suggested a pleiotropic effect of clopidogrel; however, when this drug causes platelet‐independent effects on endothelial function remains unclear. Aims: To evaluate the influence of clopidogrel on inflammatory biomarkers and adhesion molecules in human endothelial cells and the role of nitric oxide (NO) in this process. Methods: TNF‐α‐induced human umbilical vein endothelial cells (HUVEC) were exposed to clopidogrel. Gene expression and protein expression of ICAM‐1, P‐selectin, IL‐8, IL‐6, and MCP‐1 were evaluated by qPCR, flux cytometry, or milliplex technology. Expression of endothelial nitric oxide synthase ( NOS3 ) and NO release were also evaluated. Influence of clopidogrel was further evaluated in NOS3 downregulated HUVEC by RNAi. Results: Clopidogrel at 20 μmol/L induced NO release in HUVEC after 24‐hours treatment. Gene expressions of inflammatory markers IL‐8 and MCP1 were reduced after clopidogrel treatment ( P <.05); however, only MCP‐1 remained reduced at protein level. IL‐6 was not modified by clopidogrel treatment. Gene expression and protein expression of ICAM‐1 were diminished by 24‐hours clopidogrel exposure, whereas P‐selectin was not modified. NOS3 downregulated HUVEC model revealed that ICAM‐1 modification by clopidogrel is dependent of this via, whereas MCP‐1 is modulated in an NO‐independent form. Conclusions: Our results support new evidence for pleiotropic effects of clopidogrel on inflammation and endothelial function. Reduction in ICAM‐1 and MCP‐1 in human endothelium is an important extent of the use of this drug for treatment of cardiovascular diseases, and NO has an important role in this process.